Three new goatfishes of the genus Upeneus (Mullidae) from the Indo-Pacific, with a redescription of colour patterns in U. margarethae - Uiblein, Franz; Gledhill, Daniel C.; Pavlov, Dimitri A.; Hoang, Tuan Anh; Shaheen, Shaker (Zootaxa, 2019)
For the goatfish genus Upeneus Cuvier 1829 (Mullidae), a new taxonomic species group called the “margarethae group” is established which can be distinguished from the six species of the most similar “tragula group” by a combination of the following characteristics: absence of dark pigmentation in the area of the first dorsal-fin tip, 21–25 total gill rakers and 28–30 lateral-line scales. Initially, three recently-described species have been included in the margarethae group: Upeneus margarethae Uiblein & Heemstra, 2010, known from the Indian Ocean including the Red Sea and from the Arafura Sea (W Pacific), U. mouthami Randall & Kulbicki, 2006, from New Caledonia and Vanuatu (W Pacific), and U. randalli Uiblein & Heemstra, 2011, from the Arabian/Persian Gulf and the inner Gulf of Oman (NW Indian Ocean). The present taxonomic review of the margarethae group analyses a large data set of 41 morphometric, 10 meristic and many colour characters obtained from 279 preserved goatfish specimens and 166 fresh-colour photos (plus a fresh-colour drawing). For the nominal species of the group, U. margarethae, a redescription of the colour patterns is provided and new records for Myanmar, Andaman Sea (NE Indian Ocean) and the Gulf of Carpentaria, N Australia (W Pacific), are reported. Three new species are described: U. caudofasciatus n. sp. from the area of the Great Barrier Reef to Torres Strait off NE Australia (Coral Sea, W Pacific), U. gubal n. sp. from the S Gulf of Suez (Northern Red Sea), and U. heterospinus n. sp. from S Indonesia to Singapore, the Gulf of Thailand, Vietnam, Philippines, China, Taiwan and Japan (W Pacific). A comprehensive alpha-taxonomic approach is adopted, considering population differences as well as intraspecific size-related variation in morphology and colour patterns by splitting the data set into two size classes, adults (≥ 65 mm SL) and smaller subadults. Inter- and intraspecific comparisons include statistical analyses for species and population with sufficiently large samples sizes (n ≥ 20). Colour-pattern characterization and analysis are based on photos of recently collected and deceased fish (partly associated with voucher specimens), photos obtained from active or resting fishes in situ or in a tank, and inspection of pigmentation patterns retained in preserved specimens. Species differences are elaborated under consideration of distribution patterns and the characteristics found in the closest-most population of widely distributed species such as U. margarethae, resulting in clear and consistent distinction among the six species in single or in a combination of several characteristics. Comparisons among size classes revealed species-specific patterns in morphometric, meristic and colour changes with increasing size. One species, U. heterospinus n. sp., has seven or eight spines in the dorsal fin which occur in balanced ratio across populations. This is a unique characteristic for Upeneus species which usually have either seven or eight dorsal-fin spines, respectively. The best distinction of Upeneus heterospinus n. sp. from all other congeners is reached by combined examination of dorsal-fin spines with several other characters such as barbel colour, presence of a mid-lateral body stripe, pigmentation patterns (partly retained also in preserved fish), gill-raker and pectoral-fin ray numbers, and body-shape variables. The high degree of overall morphological differentation among the three most common species U. caudofasciatus n. sp., U. heterospinus n. sp. and U. margarethae, as revealed by the statistical comparisons, strongly contrasts with a still signficant, but much lower degree of differentiation among populations. The diagnostic characteristics of the margarethae group are updated and the importance to use the results of this taxonomic review in ongoing fisheries-related and ecological research is emphasized. Requirements for future taxonomic research featuring the stunning diversity of the goatfish genus Upeneus are also discussed.